The inbox exercise: Performance evaluation at ConsultSinga (A) and (B) - VADERA, Abhijeet K. (Institutional Knowledge at Singapore Management University, 2024)
In this Inbox Exercise, students are to assume the role of Kiran Kamdar, a new analyst at a hypothetical consultancy company called ConsultSinga, and respond to emails in his inbox. These include invitations from the boss to play golf during the weekend and from co-workers for after-work drinks or to their homes. There are also various work-related requests including assistance with intern recruitment, help with budgeting, suggestions to amend billing hours, commenting on co-workers’ job roles, assessing a secretary’s performance, and recommending candidates for hiring. In addition, there are also emails from HR, the IT department, and the spouse. Students must answer all questions within a specified time limit. Their performance will be evaluated after completing two rounds of replies, one in Part A, and another in Part B. The exercise is designed to simulate situations where individuals are expected to identify ethical issues and make decisions under time constraints. Students can respond using either pen and paper or interactively using the Excel spreadsheets provided. This collection of exercises aims to enhance students’ ethical awareness and help them make informed decisions ethically. Through a distinction of ‘want’ versus ‘should’ and theories on moral licensing and moral compensation, they explore the various factors (such as licensing effects, self-control, closeness to future self, etc.) that influence their ethical decision-making thought process. The scenarios also illustrate how social networks may influence unethical behaviour in the workplace.